PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP BIAYA MODAL EKUITAS - Anum Anindita Rahmah; Rr Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2020)
This study aims to analyze and obtain evidence regarding the relationship between audit committee characteristics and cost of equity capital. Cost of equity capital as dependent variable was calculated using CAPM method. Audit committee characteristics as independent variable consist of size, meeting frequencies, independency, and accounting competence. In addition, company size and leverage were included as control variables. This study uses puposive sampling techniques with all companies listed on Indonesian stock exchange 2017 as participants. Hypothesis testing in this study using multiple linear regression involving 384 companies as samples. The examination results show positive relationship between the size of audit committee and cost of equity capital.